Strategi Kepemimpinan Bisnis di Era Digital - Shaqiela, Adzkya; Akmal, Hikmatul; Gumilang, Cahaya; Mauraksa, Ikram Rabbani; Anugrah, Ridho; Sunarya, Erry (Universitas Pahlawan Tuanku Tambusai, 2024)
In the ever-evolving digital era, business leadership faces new challenges and opportunities that require innovative and adaptive strategic approaches. This article explores various leadership strategies that are effective in dealing with rapid technological change, globalization, and market dynamics. The main focus is on developing digital skills, leveraging data and analytics for decision making, as well as the importance of transforming organizational culture towards a more collaborative and flexible work environment. With case studies from a variety of industries, this article illustrates how business leaders can inspire and guide their teams through disruptive change, and ensure long-term sustainability and growth. Apart from that, the role of ethical and values-based leadership in building trust and reputation in the digital world is also discussed. In conclusion, effective leadership in the digital era requires a combination of technical skills, adaptability and commitment to continuous innovation.